Using a Personal Digital Assistant for Self-monitoring Influences Diet Quality in Comparison to a Standard Paper Record among Overweight/obese Adults - Acharya, Sushama D. (2011)
Self-monitoring has traditionally been done using paper record (PR), which can be tedious and burdensome. A personal digital assistant (PDA) with dietary software may provide an alternative to a PR. The study aimed to describe the differences in dietary changes at 6 months between participants randomly assigned to use a PR or PDA for self-monitoring in a clinical trial of weight loss treatment. Self-monitoring adherence, change in weight and diet were assessed between 2006 and 2009. The sample (N=192) was 84% female and 78% White with a mean age of 49 years and body mass index of 34.0 kg/m(2). At baseline, the groups did not differ in energy intake, % calories from fat and number of servings of the examined food groups. At 6 months, both groups had significant reductions in weight, energy intake and % calories from total fat and saturated fatty acids (Ps <0.001); no between-group differences were found. Compared to the PR group, the PDA group significantly increased consumption of fruit (P=0.02), vegetables (P=0.04), and decreased consumption of refined grains (P=0.02). Interactions between self-monitoring and the two groups were found in relation to changes in % calories from total fat (P=0.02), monounsaturated fatty acids (P=0.002) and trans-fatty acids (P=0.04). Frequent self-monitoring was significantly associated with total sugar (P=0.02) and added sugar (P=0.01) intake in both groups. Our findings suggest that the use of PDA for self-monitoring might improve self awareness of behavior and dietary changes.